STUDENTS’ STRATEGIES IN ENHANCING VOCABULARY - Yisrel Nani Sallata (English Language Teaching Methodology, 2022)
The purpose of this study was to find out the learning strategies used by seventh-semester students majoring in English education at UKI Toraja in enhancing their vocabulary through interviews. In this study, the researcher used qualitative research methods. The population of this study was the seventh-semester English students majoring in FKIP UKI Toraja. To collect data, the researcher used observation and then interviews that were conducted in person and by telephone and recorded via cellphone. The researcher used cluster sampling in selecting samples, and there were 20 students as respondents. The obtained data were analyzed by data reduction, data display, and drawing or verifying conclusions.Based on the results of the research, the researcher concludes that the seventh semester students of the English education department of the FKIP UKI Toraja faculty use various learning strategies to improve their vocabulary. The learning strategies they use are determination strategies, social strategies, memory strategies, cognitive strategies, and metacognitive strategies.